Current Challenges in Financial Regulation - Claessens, Stijn (World Bank, Washington, DC, 2012)
Financial intermediation and financial services industries have undergone many changes in the past two decades due to deregulation, globalization, and technological advances. The framework for regulating finance has seen many changes as well, with approaches adapting to new issues arising in specific groups of countries or globally. The objectives of this paper are twofold: to review current international thinking on what regulatory framework is needed to develop a financial sector that is stable, yet efficient, and provides proper access to households and firms; and to review the key experiences regarding international financial architecture initiatives, with a special focus on issues arising for developing countries. The paper outlines a number of areas of current debate: the special role of banks, competition policy, consumer protection, harmonization of rules-across products, within markets, and globally-and the adaptation and legitimacy of international standards to the circumstances facing developing countries. It concludes with some areas where more research would be useful.